2022
DOI: 10.3389/fnhum.2022.877249
|View full text |Cite
|
Sign up to set email alerts
|

The Eye Pupil Adjusts to Illusorily Expanding Holes

Abstract: Some static patterns evoke the perception of an illusory expanding central region or “hole.” We asked observers to rate the magnitudes of illusory motion or expansion of black holes, and these predicted the degree of dilation of the pupil, measured with an eye tracker. In contrast, when the “holes” were colored (including white), i.e., emitted light, these patterns constricted the pupils, but the subjective expansions were also weaker compared with the black holes. The change rates of pupil diameters were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The yellow stimulus was selected to match that used in the seminal human pupillometry study (Laeng & Endestad, 2012), while the cyan one was chosen to check for a possible bluish bias in this brightness illusion, as already reported in previous studies (Suzuki, Minami, Laeng, et al, 2019; Thurman et al, 2021). Finally, the magenta was retained based on a previous study with illusory expanding holes since this illusion was found to be the most effective with a magenta background (Laeng et al, 2022). Selecting these 3 colors also permitted to sample the hue space homogenously (with a distance of 120° between all 3 colors in hue space).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yellow stimulus was selected to match that used in the seminal human pupillometry study (Laeng & Endestad, 2012), while the cyan one was chosen to check for a possible bluish bias in this brightness illusion, as already reported in previous studies (Suzuki, Minami, Laeng, et al, 2019; Thurman et al, 2021). Finally, the magenta was retained based on a previous study with illusory expanding holes since this illusion was found to be the most effective with a magenta background (Laeng et al, 2022). Selecting these 3 colors also permitted to sample the hue space homogenously (with a distance of 120° between all 3 colors in hue space).…”
Section: Methodsmentioning
confidence: 99%
“…Another open question is whether this phenomenon plays an adaptative role or whether it is simply an epiphenomenon without any significant function. Recently, it has been proposed that the influence of cognitive/perceptual factors on pupil responses might reflect an anticipation mechanism of probable, upcoming, light stimulation that could guarantee efficient protection against light over-exposure or simply being temporarily dazzled by light, hence suggesting the possibility that this putative predictive response represents an adaptive mechanism that enhances survival in our species (Laeng et al, 2022). In this case, natural selection has likely promoted the same mechanism in a majority of species with movable pupils.…”
Section: Introductionmentioning
confidence: 99%
“…Disjointed sensory clues coalesce into coherent representations of a first-person, unified perspective [ 42 , 49 , 50 , 51 ]. Intelligent systems’ fundamental unity [ 27 ] permits predictive processing [ 4 ], the optimization of action repertoire between the past and the future [ 8 , 52 ], and between memory and expectation. The stationary-action principle states that the action for actual trajectories is a minimum.…”
Section: The Temporal Mindmentioning
confidence: 99%
“…Shannon refers to communication systems as the first kind of system, but intelligent systems [ 54 ], which rely on temporal computation [ 4 ], can control the future. Wissner-Gross and Freer [ 54 ] have shown a physical connection between adaptive behavior and entropy maximization.…”
Section: Thermodynamic Regulation Of the Neural Systemmentioning
confidence: 99%
See 1 more Smart Citation